Risk stratification of severe sepsis patients in the emergency department - Chen, C‐C (BMJ Group, 2006)
OBJECTIVE: To determine the efficacy of the Mortality in Emergency Department Sepsis (MEDS) score in the stratification of patients who presented to the emergency department (ED) with severe sepsis. METHODS: Adults who presented to the ED with severe sepsis were retrospectively recruited and divided into group A (MEDS score <12) and group B (MEDS score ⩾12). Their outcomes were evaluated with 28 day hospital mortality rate, length of hospital stay, Kaplan‐Meier survival analysis, and receiver operating characteristic (ROC) analysis. Discriminatory power of the MEDS score in mortality prediction was further compared with the Acute Physiology and Chronic Health Evaluation (APACHE) II model. RESULTS: In total, 276 patients (44.6% men and 55.4% women) were analysed, with 143 patients placed in group A and 133 patients in group B. Patients with MEDS score ⩾12 had a significantly higher mortality rate (48.9% v 17.5%, p<0.01) and higher median APACHE II score (25 v 20 points, p<0.01). Significant difference in mortality risk was also demonstrated with Kaplan‐Meier survival analysis (log rank test, p<0.01). No difference in the length of hospital stay was found between the groups. ROC analysis indicated a better performance in mortality prediction by the MEDS score compared with the APACHE II score (ROC 0.75 v 0.62, p<0.01). CONCLUSION: Our results showed that mortality risk stratification of severe sepsis patients in the ED with MEDS score is effective. The MEDS score also discriminated better than the APACHE II model in mortality prediction.